Long-term cultivation of a neuroblastoma cell line in medium with reduced serum content as a model system for neuronal aging? - Kalka, Dorothee; Hoyer, Siegfried (Archives of gerontology and geriatrics, 1998)
Impaired energy metabolism and increased vulnerability to additional stress are some of the pivotal characteristics of the aging brain. This study was designed to establish a cell culture model for long-term investigations of some mechanisms underlying the process of aging using the neuroblastoma cell line SK-N-MC. As high serum concentrations in the culture medium are a major disadvantage for the investigation of regulatory or toxic influences, the effects of serum reduction in the culture medium on growth, viability and energy metabolism during long-term cultivation were determined. Serum reduction resulted in a decrease in the proliferation rate and in increased vulnerability of the cells, measured as release of lactate dehydrogenase into the culture medium. The rates of glucose consumption and lactate production were elevated, whereas the energetic state was markedly compromised, as was obvious from a 40% reduction of creatine phosphate. The observed increased vulnerability and the decreased energy state of the SK-N-MC cells were even more pronounced after induction of free radicals by addition of FeSO4 to the medium with reduced serum content. Increased oxidative stress was indicated by elevated cellular contents of glutathione both after serum reduction and after incubation with FeSO4. It is concluded that the SK-N-MC cells cultured chronically in medium with low serum content display biochemical characteristics that are similar to those observed in aging studies with animal models.
Gesehen am 20.11.2025
Online verfügbar: 23. November 1998